(untitled) (Contemporary Central & East European Law, 2024)
The life and work of Professor Stanisław W.A. Kasznica follow values in a special way. This is indicated by his scientific output, his curriculum vitae and also the history of his family. This article analyses S. Kasznica’s textbook Polskie prawo administracyjne: pojęcia i instytucje zasadnicze (Polish Administrative Law: Basic Concepts and Institutions), 2nd Edition, Poznan 1946 to determine how, in his scientific output, S.W.A. Kasznica assigned values to the legal and juridical institutions he described. The first method is the contextual “indirect” assignment of values to a given legal institution (i.e. resulting from the general overtone meaning of a given passage of text). The second method of institutionalising value refers to value as transcendental. The third method used is the direct criticism or negation of certain institutions in a way that indicates that their antithesis is some kind of good. The fourth method of institutionalising values is to define certain institutions by directly indicating that the institution serves values. This is, in other words, the introduction of certain values into the content of a legal institution. The fifth method of value institutionalisation by S. Kasznica is based on signalling how certain anti-values objectively external and internal to the law can nevertheless be beneficial to the law. Of course, these observations are made on the basis of an analysis of the practice of public authorities and take the form of statements tinged with a slight cynicism. S. Kasznica points out in this case how the “slowness”, or in other words the procedural incompetence of the parliamentary legislature, can peculiarly counteract the inflation of the law.